Oxidative Stress and the Pathophysiology and Symptom Profile of Schizophrenia Spectrum Disorders - Murray, Alex J.; Rogers, Jack C.; Katshu, Mohammad Zia Ul Haq; Liddle, Peter F.; Upthegrove, Rachel (Frontiers in Psychiatry, 2021)
Psychosis is associated with increased levels of oxidative stress, as reflected by an increase in the concentrations of damaging reactive species and a reduction in anti-oxidant defences to combat them. Evidence has suggested that whilst not the likely primary cause of psychosis, increased oxidative stress may contribute to declining course and poor outcomes associated with psychosis. Here we discuss how oxidative stress may be implicated in the aetiology of psychosis and examine how current understanding relates associations with symptoms, potentially via lipid peroxidation induced neuronal damage. We argue that oxidative stress may be a good target for future pharmacotherapy in psychosis and suggest a multi-step model of illness progression with oxidative stress involved at each stage.